CO2 Reforming of CH4 on Mesoporous Alumina-Supported Cobalt Catalyst: Optimization of Lanthana Promoter Loading - Tran N.T.; Kumar P.S.; Van Le Q.; Van Cuong N.; Phuong P.T.T.; Jalil A.A.; Sharma G.; Kumar A.; Sharma A.; Ayodele B.V.; Abidin S.Z.; Vo D.-V.N. (Springer, 2023)
Alumina; Aluminum oxide; Carbon dioxide; Catalyst supports; Catalytic reforming; Cobalt; Crystallite size; Fischer-Tropsch synthesis; Lanthanum oxides; Physicochemical properties; Alumina-supported cobalt catalyst; Carbon deposition; Catalytic performance; CO2 reforming of methane; Fischer-Tropsch reaction; Liquid hydrocarbon fuel; Mesoporous alumina; Reactant conversion; Loading